Women’s Political Representation in the Palu City DPRD: Access, Participation, and Structural-Cultural Barriers - Safithri, Ritha; Wahyu Wiranto; Hakim, Abd; Patta, Abdul Kadir; Suriansah, Suriansah (LifeSciFi, 2026)
This study examines the existence of women legislators in the Palu City Regional People’s Representative Council (DPRD), which remains a crucial issue in local democracy practices despite the normative guarantee of gender equality. This study aims to examine the presence of female legislators in the Palu City DPRD, in terms of representation, political roles, and the structural and cultural challenges they face. The study uses a descriptive qualitative method with a sociological and phenomenological approach, through observation, in-depth interviews, and documentation studies of DPRD members, institutional leaders, and relevant institutional documents. The results show that Palu City has the potential socially, demographically, and in human resources for women’s involvement in politics, but this potential has not been optimally realized. Women’s representation in the Palu City DPRD remains low, access to strategic commissions is limited, and there are no women in the leadership structure, so women’s participation tends to be symbolic. The findings reveal that patriarchal culture, weak political party support, and limited strategic positions hinder the substantive role of women legislators. Therefore, strengthening affirmative policies, transforming political culture, and enhancing institutional capacity are essential to enable women legislators to promote fair and gender-responsive public policies more effectively.